2018
DOI: 10.3390/w10121774
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater-Sewer Interaction in Urban Coastal Areas

Abstract: In this paper, a study of the potential causes of the occurrence of high concentration of Enterococcus Faecalis in surface water within urban areas in dry-weather conditions (DWCs) is presented. Two hypotheses were formulated: (1) undersized sewer system; and (2) groundwater infiltration into damaged sewer pipes. In both cases, more frequent combined sewer overflows (CSOs) may occur discharging untreated sewage into surface water. To evaluate the first hypothesis, a hydraulic model of a sewer was developed ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…De Benedittis and Bertrand-Krajewski [27] reported GWI of about 20% of ADWF in Lyon, France. Liu et al [17] summarized GWI ranges as: 73% in Nante, France, 108% in Rastatt, Germany, 39% in Zurich, Switzerland, 33% in Dresden, Germany, 14-50% in Rome, Italy, and 75% in Trondheim, Norway. The values reported in the present study are within the ranges reported in some of the prior studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…De Benedittis and Bertrand-Krajewski [27] reported GWI of about 20% of ADWF in Lyon, France. Liu et al [17] summarized GWI ranges as: 73% in Nante, France, 108% in Rastatt, Germany, 39% in Zurich, Switzerland, 33% in Dresden, Germany, 14-50% in Rome, Italy, and 75% in Trondheim, Norway. The values reported in the present study are within the ranges reported in some of the prior studies.…”
Section: Discussionmentioning
confidence: 99%
“…The study area has both a wet and dry season, and although the study took place in the wet season, selection criteria were used to identify and isolate days of DWF. Other factors that can play a role in GWI include ocean tides, seasonal recharge rates, and fluctuations in nearby rivers or bodies of water [6,16,17]. Tidal effects on groundwater elevations were included in the present study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In their particular case of a barrier island aquifer lens system common in the USA Atlantic coastline, the amount of groundwater discharge to streams increased rather than resulting in a water table rise, and the tidal influence propagated further inland decreasing the depth to the fresh-salt water interface. In addition to the typical groundwater flow numerical model development, the subsurface infrastructure interactions were added and simulated (Liu et al, 2018;Su et al, 2020). The groundwater infiltration into an aging sewage system was investigated and the impact of repairs on the damaged sewer pipes was modeled.…”
Section: Assessment Methods Summarymentioning
confidence: 99%
“…Priority areas for managing I/I include low-lying areas, areas with unstable soils, areas with high groundwater, old pipe infrastructure, sewers located near storm drains, and sewers located near bodies of water. For collection systems with excessive I/I flows, potential impacts are sanitary sewer overflows (SSOs) from overloaded manholes and pump stations, and increased risk of bypasses at the wastewater treatment plant if flow capacity is exceeded [1][2][3].…”
Section: Introductionmentioning
confidence: 99%